Management Strategic During Pandemic Covid 19 - Azmi, Shamad Hasanul; Fauzi, Moch; Sujarwo, Joko (Prosiding Seminar; 2022: 2022 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.77, 2023)
With the emergence of a pandemic outbreak, quite a several strategies emerged and were used very quickly. The aim of the study is that strategy adaptation becomes valuable learning for the people involved in the organizational environment. In general, the level of loss for business people has increased, but of course, in other parts, there will also be very significant gains, especially for those who can adapt very quickly. The study used descriptive analysis of the environment in the pandemic situation literature. The result of Future social changes affects all industries, so every firm should regularly assess its strategic management, whether it is an ongoing or planned strategy.